Current development of stretchable self-powered technology based on nanomaterials toward wearable biosensors in biomedical applications - Wang, Qianqian; Sun, Xu; Liu, Chen; Wang, Chunge; Zhao, Wenjie; Zhu, Zehui; Ma, Sainan; Zhang, Sheng (Frontiers in Bioengineering and Biotechnology, 2023)
In combination with the growing fields of artificial intelligence and Internet-of-things (IoT), the innovation direction of next-generation biosensing systems is toward intellectualization, miniaturization, and wireless portability. Enormous research efforts have been made in self-powered technology due to the gradual decline of traditional rigid and cumbersome power sources in comparison to wearable biosensing systems. Research progress on various stretchable self-powered strategies for wearable biosensors and integrated sensing systems has demonstrated their promising potential in practical biomedical applications. In this review, up-to-date research advances in energy harvesting strategies are discussed, together with a future outlook and remaining challenges, shedding light on the follow-up research priorities.